Optimasi Biaya Promosi Sepeda Motor Yamaha dengan Menerapkan Metode Simpleks (Studi Kasus: PT. Alfa Scorpii Pematangsiantar) - Demetria Delima Sinaga (Journal of Information System Research (JOSH), 2020)
Optimization is a step called to determine the profit and loss of a company in its activities. This optimization is related to yield and production problems that often occur in a company. PT. Alfa Scorpii Pematangsiantar has objects that are marketed through marketing and sales counters. The object being marketed consists of three parts, namely a sports motorcycle, an automatic motorcycle, and a motorcycle. The problem of determining the cost of promotion in the Pematangsiantar Yamaha show room is still determined based on estimates. Marketing manager incurs sales costs based on several factors that influence such as employee costs in marketing motorbikes, promotion costs in the form of brochures of motorcycle types, prices offered. The amount of sales costs must also be based on the number of units of motorcycles sold, if it is reduced, the company will suffer losses, and sales costs must always be incurred during the motorcycle sales process will be minimized, if sales go up, the company will experience profits, then sales costs can maximized. To optimize sales costs to make a profit, the determination of sales costs can be completed using a linear program model. Several ways to solve problems with the linear program model, including being solved by the Simplex Method